Functions of Social and Cultural Activities of Culture Institutions as Social Centers - M. S. Yakushkina (Научный диалог)
The results of the analysis of functions of social and cultural activities of culture institutions as social centers are presented. The following functions are distinguished: communicative, cultural-educational, creative, recreational-health, financial-economic, legal security and protection of constitutional rights and freedoms of the individual, etc. Special attention is paid to the conditions of realization of pedagogical potential of culture institutes. It is proved that socio-cultural functions of culture institutions as social centres complement each other and form the socio-cultural activities. The classification of the functions of social and cultural activities is also proposed. The research urgency is caused by modern social development strategy, which involves the organization of uniting the efforts of various public institutions aimed at improving the socio-educational practices. The novelty of this study is seen in the fact that the functions of social and cultural activities of culture institutions as social centers are identified and analyzed subject to the conditions of the realization of their pedagogical potential. The author dwells on the fact that the functions of social and cultural activities determine the content of training of organizers and experts of this activity and their special competence. It is shown that professionals should learn to be sociable, ready to empathize with other people. The question is raised that they must have the ability to predict, to develop rapidly constructive solutions, to have managerial skills in small groups, etc.